Estudo dos parâmetros autonômicos cardiovasculares em ratos wistars submetidos à suplementação crônica de chá verde e treinamento físico - SANTOS, Wellington Lourenço Mendes dos (2016)
Various studies have shown that green tea has a high number of flavonoids known as catechins, which help in lowering body fat, and in the prevention and treatment of obesity and related diseases such as cardiovascular. The other hand, previous studies have shown that green tea high consumption may cause high sympathetic activity, which is related to the genesis and maintenance of hypertension and is also associated with several cardiovascular diseases. Although of the literature provides evidence that green tea and exercise training are important to perfect functioning of cardiovascular system, until now, few studies in this area have been conducted to assess the effects of the association between green tea and exercise training on cardiovascular autonomic function. Thus, this study aimed to evaluate the effects of administration of green tea combined with exercise training on cardiovascular autonomic modulation in wistar rats. For this, the animals were divided into four groups: sedentary control group (SEDcon, n=10), trained control group (TRAcon, n=08), sedentary green tea group (SEDtea, n=16) and trained green tea group (TRAtea, n=09). Two grams of vegetable green tea diluted in 01 liter of water were administered (infusion method) and swimming exercise training (increasing volume and intensity). After eight weeks of protocol we evaluated the baseline heart rate (HR) and blood pressure (BP), cardiac autonomic tone, HR variability (HRV), systolic BP (SBPV) and diastolic (DBPV) and relative cardiac weight. For all the results we used a significance level of 5%. No difference was observed in body weight between all animals group during the weeks of exercise training. The animals of the TRAcon, SEDtea and TRAtea exhibited resting bradycardia compared to SEDcon. The green tea was able to reduce BP levels in both SEDtea and TRAtea groups, as well as, an increased in HRV of time domain and the values of spectral component of high frequency band (HF) of frequency domain. On the other hand, the green tea reduces the variance of DBPV and of the sympathetic autonomic modulation in SBPV and DBPV. The animals of TRAcon and SEDtea groups showed a reduced cardiac autonomic tone. The groups of animals that received green tea had a lower cardiac weight, both absolute and relative. So, our results suggest that the chronic administration of green tea can provide cardiovascular autonomic changes in Wistar rats, marked by increase in parasympathetic activity on the heart. Our data also indicate that non-pharmacological strategies, such as exercise and green tea are effective, however, can’t result in the raise of cardiovascular autonomic effects.